Taninos condensados de acácia negra (Acacia mearnsii) na alimentação de ruminantes - Avila, André Sanches de (2018)
Additives use to modify ruminal fermentation is an alternative to improve animal productivity. Among the most used additives, plants extracts, as the condensed tannins that according to the level and source used, it can bring benefits to ruminant production. It was conducted a study to evaluate the use of condensed tannins and its effects on lactating Holstein cows performance. It was used five cows in a Latin square design 5x5, where the treatments were levels of condensed tannins from Acacia mearnsii (0, 5, 10, 15 and 20 g/kg of DM of total diet), periods consisted in 14 days of adaptation and 6 days for sampling. Condensed tannins use did not influence the dry matter intake, however, it was found a quadratic effect of tannins in the digestibility of dry matter and NDF with maximum values in 12,2 and 11,4 g/kg of tannins in DM respectively. It did not occur major effects on blood parameters and microbial protein synthesis and milk production in kg/day, however, there was a reduction in milk production corrected to fat and energy and in casein contents, being an undesirable effect in animals’ performance. In another study carried out it was evaluated tannin levels to feed cannulated jersey steers. The design was a Latin square 5x5 with five animals and treatments were related to the inclusion levels of Acacia mearnsii (0, 5, 10, 15 and 20 g/kg of DM). The inclusion of tannins did not influence the nutrients digestibility except for CP that decreases linearly. There was a linear reduction in ruminal pH values, that is related to tannins pH. Population of ruminal protozoans and gender evaluation in the rumen were not influenced as well as the ruminal NNH3 nitrogen levels were not influenced by tannins. Inclusion of condensed tannins reduces the proportion of acetic acid and did not influence the ruminal protozoa population, however it reduces the apparent crude protein digestibility.